Synthesis, Characterization and Spectral Studies of Fe(lll) and Cr(lll) Schiff base Complexes with Acetoacetanilidepropylenediamine - Santhi, S.; Harikumar, B.; Radhakrishnan Namboori, C.G. (Asian Journal of Chemistry, 2011)
The Fe(lll) and Cr(lll) complexes of Schiff base derived from acetoacetanilide and propylenediamine, [MXL(H2O)], where LH2 = acetoacetanilidepropylenediamine, M = Fe3+ or Cr3+ and X = Cl–, NO3–, NCS–, CH3COO– or ClO4–, have been synthesized in alcohol and characterized by elemental analysis, electrical conductance in non-aqueous solvents, infrared and electronic spectra as well as magnetic susceptibility measurements. In these complexes, ligand LH2 acts as dibasic tetradentate ligand coordinating through the two azomethine nitrogen atoms and the two enolizable carbonyl group of acetoacetanilide moiety. The molar conductance of the complexes in DMF and DMSO are in the range of non-electrolytes. The electronic spectra and molar magnetic moment of the complexes show a distorted octahedral environment around the metal ion. Presence of water coordination in the complexes is confirmed by the endothermic bands observed in DTA curve in the temperature region where the TGA curves indicates loss in weight.